2020
DOI: 10.3389/fbuil.2020.590114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Infill Walls in the Dynamic Behavior and Seismic Upgrade of a Reinforced Concrete Framed Building

Abstract: Masonry infill walls are commonly used in the frames of reinforced concrete (RC) buildings around the world. The seismic performance of these buildings is strongly affected by the presence of the infill walls and partitions, as shown by the post-earthquake damage in many cases. The effect of these components is particularly important for RC frame constructions underdesigned for seismic actions that usually are characterized by deformable frames magnifying the contribution of the infill walls to the seismic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The main limitation of the study is that weight of the infill wall is considered and no actual modeling of the wall is done during analysis. Infill wall plays a significant role in the seismic performance of structures [12]. Soil structure interaction is not considered during the study and the base of the structure is considered fixed.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the study is that weight of the infill wall is considered and no actual modeling of the wall is done during analysis. Infill wall plays a significant role in the seismic performance of structures [12]. Soil structure interaction is not considered during the study and the base of the structure is considered fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Dhakal et al [79] adopted modal parameters obtained from in-situ AVTs to calibrate FE models of two four-storey infilled RC frame building in Nepal, and, in addition to the infills, they also calibrate the soil deformability to account for the soil-structure interaction. De Angelis and Pecce [80,81] calibrated FE models of buildings tested with AVTs and also considering the internal partitions, that are modelled within the refined numerical models. Asgarian and McClure [82] performed model calibrations of two infilled RC hospital buildings in Canada based on AVT recordings on both buildings, as well as Mora et al [83], who adopted a genetic algorithm to calibrate the infill mechanical properties of a real building built around 1950s.…”
Section: Effects Of Infill Masonry Walls On the Dynamic Behaviour Of ...mentioning
confidence: 99%
“…At last, few authors investigated the effects of non-structural components and equipment on the building dynamic [78] FVs (shaker) EDS Dhakal et al [79] AVTs Shell De Angelis and Pecce [80] AVTs EDS De Angelis and Pecce [81] AVTs EDS Asgarian and McClure [82] AVTs EDS and Shell Mora et al [83] AVTs EDS and Shell Pan et al [84] AVTs Shell Yun et al [85] AVTs EDS Zhou et al [86] AVTs EDS and Shell Su et al [87] AVTs Shell Aras [88] AVTs and ILTs (Hammer) Shell O'Reilly et al [89] AVTs and FVs (Earthquakes) EDS But and Omenzetter [90] FVs (Earthquakes) EDS behaviour. It is the case of Alembagheri et al [91], who dynamically tested a full-scale laboratory 3-D steel module with different gypsum-board walls, or Wang et al [92], who tested a full-scale steel structure specimen over a shaking table focusing also on the effects of interior partitions and plant piping.…”
Section: Effects Of Infill Masonry Walls On the Dynamic Behaviour Of ...mentioning
confidence: 99%
“…Over the past several decades, extensive research works have been carried out to investigate the seismic behaviour of infilled frames especially for RC structures (e.g., Alwashali et al 2019;Cavaleri and Di Trapani 2014;De Angelis and Pecce 2020;Furtado et al 2019;Morandi et al 2018;Rodrigues et al 2018;Tan et al 2018)). In the experimental tests of infilled steel frames, some influential parameters were studied, and the test results showed that the structural stiffness and strength were significantly related to the rigidity of the steel beam-column connection (Mohammadi and Emami 2019) and the connection type between the infill and frame (Liu and Manesh 2013).…”
Section: Introductionmentioning
confidence: 99%